NF-κB Activation and Severity of Gastritis in Helicobacter pylori-Infected Children and Adults - Bontems, Patrick; Aksoy, Ezra; Burette, Alain; Segers, Valérie; Deprez, Carine; Mascart, Françoise; Cadranel, Samy (Helicobacter (Cambridge, Mass.), 2014)
Background In contrast to adults, Helicobacter pylori gastritis in children is reported as milder and ulcer disease as uncommon, but unequivocal data are lacking. Objectives To compare the frequency of gastro‐duodenal ulcers in children and adults as well as the proportion of Helicobacter pylori infection in these patients and to study the effect of chronological age on NF‐κB activation and on severity of gastritis. Design Patients referred in one pediatric and one adult facility for upper GI endoscopy were included. Gastric biopsies were obtained in consecutive Helicobacter pylori‐infected patients and age‐matched negative controls for immunohistochemistry and electrophoresis mobility shift assay. Three age groups were defined: younger than 8 years, 8–17 years, and adults. Results Peptic ulcer disease was less frequent in children and less frequently associated with Helicobacter pylori infection. When comparing infected subjects to controls, densities of neutrophils and CD20 cells in the lamina propria increased in all age groups, CD3 cells increasing only in patients older than 8 years and CD8 cells only in adults. NF‐κB‐p65‐positive cells were also increased only in infected adults as well as NF‐κB‐binding activity. A positive correlation was found between age and densities of neutrophils and CD3, but not of CD8 or CD20 cells. Conclusion Peptic ulcer disease was less frequent in children and less frequently caused by Helicobacter pylori infection. The different clinical outcome of the infection in children can be the consequence of the lower mucosal immune response.